2022
DOI: 10.1186/s12917-022-03197-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and pathogenesis of Staphylococcus aureus from bovine mastitis: current understanding and future perspectives

Abstract: Staphylococcus aureus is a leading cause of bovine mastitis worldwide. Despite some improved understanding of disease pathogenesis, progress towards new methods for the control of intramammary infections (IMI) has been limited, particularly in the field of vaccination. Although herd management programs have helped to reduce the number of clinical cases, S. aureus mastitis remains a major disease burden. This review summarizes the past 16 years of research on bovine S. aureus population genetics, and molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 202 publications
2
73
0
1
Order By: Relevance
“…Thereby, MGEs cause gene gain and loss, and they can subsequently lead to genetic adaption to new niches [ 18 ]. Evolutionary studies of S. aureus strains have revealed that some MGEs and virulence genes are host-specific [ 19 , 20 ]. To date, several of such bovine-specific virulence factors are described, for instance some leukotoxins, which are associated with lytic activity against white blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, MGEs cause gene gain and loss, and they can subsequently lead to genetic adaption to new niches [ 18 ]. Evolutionary studies of S. aureus strains have revealed that some MGEs and virulence genes are host-specific [ 19 , 20 ]. To date, several of such bovine-specific virulence factors are described, for instance some leukotoxins, which are associated with lytic activity against white blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus and S. intermedius are prevalent coagulase-positive staphylococci species involved in bovine mastitis (Wald et al, 2019), particularly S. aureus and S. intermedium also isolated in the present study. Coagulasepositive staphylococci has been described as the most pathogenic microorganisms related to mastitis in cows and heifers in Canada and the United States (McParland et al, 2019;Campos et al, 2022). This group of bacteria often causes subclinical mastitis, with chronic evolution and refractoriness to conventional antimicrobials.…”
Section: Milk Productionmentioning
confidence: 99%
“…The difficulty in treating staphylococcal mastitis, particularly S. aureus, due to the high occurrence of this group of agents in bovine mastitis, the multidrug resistance to conventional antimicrobials, a set of virulence factors, and mechanisms of evasion of the pathogen's immune system have motivated programs for the early disposal of bovine females with mastitis by S. aureus, which cause a negative impact on herds (Campos et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“… Staphylococcus aureus continues to be recognized as one of the major and most prevalent agents of dairy cow intramammary infections worldwide ( 1 , 2 ). We report draft genome sequences of five S. aureus strains, three of which were isolated from buffalo milk and two of which were isolated from milk samples from cattle in Pakistan.…”
Section: Announcementmentioning
confidence: 99%